The Influence of Working Capital Structure on The Profitability of Manufacturing Companies Listed on The Indonesia Stock Exchange - Oktavianus Karno; Elly Lestari; Moch Nurhidayat (International Research & Development for Human Beings (IRDH), 2026)
This quantitative study looked at the relationship between three key debt ratios—the Debt to Equity Ratio (DER), the Long-term Debt to Equity Ratio (LDER), and the Debt to Assets Ratio (DAR)—and the profitability of manufacturing companies that are partially listed on the Indonesia Stock Exchange (IDX). The researchers used a purposive sample technique to choose six industrial enterprises on the IDX, and they gathered 30 financial statement data points from 2019 to 2023. Multiple linear regression analysis was the primary method used to examine the data. The study's findings demonstrate that any debt ratio alone has a statistically significant impact on profitability. Specifically, DAR, LDER, and DER had t-values of 5.095 (p < 0.05), 4.751 (p < 0.05), and 6.072 (p < 0.05), the corresponding accordingly. Furthermore, the combined influence of DAR, LDER, and DER on profitability was shown to be extremely significant with an F-value of 17.116 and an R2 of 75.2%. This suggests that when combined, these three debt ratios may account for a sizable portion of the variation in the profitability of the chosen businesses. The study concludes that an increase in these debt ratios (DAR, LDER, and DER) is associated with a larger possibility for enhanced profitability, underscoring the critical role that effective working capital management plays in enhancing a company's financial performance.